Sweetpotato Product Advancement Meeting Report for Uganda - Nakitto, M.; Serunkuma, E.; Namanda, S. (2025)
The meeting focused on involving stakeholders in Uganda in advancing promising sweetpotato clones suitable for the East African market segments, and refining sweetpotato breeding product profiles. Germplasm from CIP’s Sweetpotato Breeding Program for the East Africa region and NARO’s National Sweetpotato Breeding Program were evaluated. Breeding teams provided updates on the performance of clones in preliminary yield trials (PYT) and advanced yield trials (AYT), emphasizing yield, disease resistance, and quality traits. Key outcomes included: Recommendations for On-Farm Testing and National Performance Trials: • Two white-fleshed sweetpotato (WFSP) clones from CIP’s breeding program demonstrated a 20% higher storage root yield compared to the check clone ‘NASPOT 11’ (13.4 t/ha). • Seven WFSP clones from NARO’s breeding program showed an 18% yield advantage over ‘NAROSPOT 1’ (26.01 t/ha). Advancement of Promising Clones to Advanced Yield Trials (AYT): • Fifteen (15) WFSP clones from CIP’s breeding program, with storage root yield ranging between 27.61 t/ha (‘UGP202000303-32’) to 42.27 t/ha (‘UGP202000062-16’), were advanced to AYT. • Twelve (12) orange-fleshed sweetpotato (OFSP) clones, with storage root yield ranging between 19.03 t/ha(‘UGP202000177-8’) to 34.37 t/ha (‘UGP202000052-10’), were advanced to AYT based on the storage root yield threshold (15t/ha) for the OFSP target product profile. Refinement of thresholds in the TPP: • Threshold scores for root shape were revised to accommodate shapes suitable for packaging sweetpotato roots by traders. These achievements highlight significant progress in sweetpotato breeding and a strong commitment to delivering high-performing varieties for the region.